Peyer’s patch organogenesis is intact yet formation of B lymphocyte follicles is defective in peripheral lymphoid organs of mice deficient for tumor necrosis factor and its 55-kDa receptor - Pasparakis, Manolis (The National Academy of Sciences of the USA, 1997)
Targeted inactivation of genes in the tumor necrosis factor (TNF)/lymphotoxin (LT) ligand and receptor system has recently revealed essential roles for these molecules in lymphoid tissue development and organization. Lymphotoxin-αβ (LTαβ)/lymphotoxin-β receptor (LTβ-R) signaling is critical for the organogenesis of lymph nodes and Peyer’s patches and for the structural compartmentalization of the splenic white pulp into distinct B and T cell areas and marginal zones. Moreover, an essential role has been demonstrated for TNF/p55 tumor necrosis factor receptor (p55TNF-R) signaling in the formation of splenic B lymphocyte follicles, follicular dendritic cell networks, and germinal centers. In contrast to a previously described essential role for the p55TNF-R in Peyer’s patch organogenesis, we show in this report that Peyer’s patches are present in both TNF and p55TNF-R knockout mice, demonstrating that these molecules are not essential for the organogenesis of this lymphoid organ. Furthermore, we show that in the absence of TNF/p55TNF-R signaling, lymphocytes segregate normally into T and B cell areas and a normal content and localization of dendritic cells is observed in both lymph nodes and Peyer’s patches. However, although B cells are found to home normally within Peyer’s patches and in the outer cortex area of lymph nodes, organized follicular structures and follicular dendritic cell networks fail to form. These results show that in contrast to LTαβ signaling, TNF signaling through the p55TNF-R is not essential for lymphoid organogenesis but rather for interactions that determine the cellular and structural organization of B cell follicles in all secondary lymphoid tissues.